The interaction of methyl viologen with anionic polyelectrolytes. A study by a fluorescence quenching method - Baumgartner, E.; Bertolotti, S. G.; Cosa, J. J.; Gsponer, H. E.; Hamity, M.; Previtali, C. M. (Elsevier, 1987)
Fil: Baumgartner, E. Comisión Nacional de Energía Atómica; Argentina